FOREIGN EXPERIENCE OF STATE REGULATION OF HIGHER EDUCATION - Zastrozhnokova , I. (Theory and Practice of Public Administration, 2020)
In the field of education, there are currently three levels of government: national, regional and district. Improving the system of regional education in Ukraine is an important issue for research. The article identifies the tasks and main problematic aspects of the management of regional education in Ukraine. The concept of “learning region” is described in detail. It is noted that the successful economic development of the United States, Japan, Germany, Britain, France, Italy, Australia and other countries is based on knowledge and use of the concept of “learning regions”. The main difference between the concept of “learning regions” is that it goes beyond the obligation to provide education and training only to those who need it. Training of the entire population of the region becomes its task. As a result, a cultural and economic environment is created, which promotes the realization of human potential of all citizens, as well as an environment for innovation. It is established that the formation of the optimal model of public education management in the region should be carried out, enriching the educational process. territory, and the nature of the formation of the regional educational space in the regions and districts of Ukraine is actively influenced by exogenous and endogenous factors and processes occurring within the educational system as a whole. Education in the regional system affects the formation of not only the labor market reflects the results already achieved by graduates at this point in time in the region. The structure of the regional education system is determined, which includes state, communal, private out-of-school educational institutions, other educational institutions as extracurricular and extracurricular educational centers, clubs and associations at the place of residence, cultural-educational, physical culture-health, sports and other educational institutions, etc. The volumes of financing of the regional educational program on the example of Dnipropetrovsk region are considered. Successful public management at the regional level is designed to make education at the regional level better and more accessible.